2019
DOI: 10.1038/s41598-019-51628-5
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile clade 3 (RT023) have a modified cell surface and contain a large transposable island with novel cargo

Abstract: The major global pathogen Clostridium difficile (recently renamed Clostridioides difficile) has large genetic diversity including multiple mobile genetic elements. In this study, whole genome sequencing of 86 strains from the poorly characterised clade 3, predominantly PCR ribotype (RT)023, of C. difficile revealed distinctive surface architecture characteristics and a large mobile genetic island. These strains have a unique sortase substrate phenotype compared with well-characterised strains of C. difficile, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In Clostridium kluyveri , Seedorf et al identified a siderophore biosynthetic locus and further showed a color change in the Chrome Azurol S (CAS) assay when the strain was grown on iron restricted media (41). The genome of Cd630 does not encode for siderophore biosynthesis genes, but a siderophore locus has been identified in genomes of some C. difficile isolates (11) suggesting that, similar to aerobic bacteria, the majority of anaerobes may use xenosiderophores, while select strains produce their own siderophore(s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Clostridium kluyveri , Seedorf et al identified a siderophore biosynthetic locus and further showed a color change in the Chrome Azurol S (CAS) assay when the strain was grown on iron restricted media (41). The genome of Cd630 does not encode for siderophore biosynthesis genes, but a siderophore locus has been identified in genomes of some C. difficile isolates (11) suggesting that, similar to aerobic bacteria, the majority of anaerobes may use xenosiderophores, while select strains produce their own siderophore(s).…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of siderophores is predicted to be vast (>500 types of siderophores), and siderophores are categorized based on general structure into four groups: hydroxamate, catecholate, phenolate, or mixed (9, 10). While siderophore biosynthesis genes have been identified in some Clade 3 C. difficile genomes, most strains of C. difficile , including the lab strain Cd630, do not encode for siderophore biosynthesis genes (11). The presence of two putative siderophore transporters, in the absence of siderophore biosynthesis genes, suggests most C. difficile strains likely use siderophores produced by other members of the gut microbiota, also known as xenosiderophores.…”
Section: Introductionmentioning
confidence: 99%
“…91,92 Clostridium difficile has been hypothesized to import siderophores produced by other microorganisms, but not to produce them. However, a recent study conducted by Shaw et al 137 identified a large genetic island from the genome of clade 3-associated strains of C. difficile, which, among other peptides, is predicted to code for the biosynthesis of a Yersiniabactin-like siderophore.…”
Section: Uptake Of Free Inorganic Ironmentioning
confidence: 99%
“…For example, ICE often encode resistance to antibiotics; e.g., Tn916, and Tn5397 (tetracycline resistance). A large ICE, 023_CTnT found in C. difficile clade 3 strains contains genes encoding a sortase, putative sortase substrates, lantibiotic ABC transporters and a putative siderophore biosynthetic cluster (Shaw et al, 2019). Similar genes are found throughout the gut microbiome indicating that ICE have a role in allowing organisms to adapt to their local environment and can transfer through the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%